2015
DOI: 10.1093/cercor/bhv041
|View full text |Cite
|
Sign up to set email alerts
|

Attention Stabilizes Representations in the Human Hippocampus

Abstract: Attention and memory are intricately linked, but how attention modulates brain areas that subserve memory, such as the hippocampus, is unknown. We hypothesized that attention may stabilize patterns of activity in human hippocampus, resulting in distinct but reliable activity patterns for different attentional states. To test this prediction, we utilized high-resolution functional magnetic resonance imaging and a novel "art gallery" task. On each trial, participants viewed a room containing a painting, and sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
153
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(169 citation statements)
references
References 62 publications
16
153
0
Order By: Relevance
“…Two recent human fMRI studies (16,17) have demonstrated that HPC representations, as evidenced in voxel activation patterns, are distinct for different task states. In these studies, searching through room images for a particular style of wall art evoked distinct HPC patterns relative to searching the same room images for a particular room layout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent human fMRI studies (16,17) have demonstrated that HPC representations, as evidenced in voxel activation patterns, are distinct for different task states. In these studies, searching through room images for a particular style of wall art evoked distinct HPC patterns relative to searching the same room images for a particular room layout.…”
Section: Discussionmentioning
confidence: 99%
“…First, HPC rapidly learns (13), an ability important for updating conceptual representations in the face of changing goals. Second, HPC has also been shown to activate representations that are goal relevant (14)(15)(16)(17)(18)(19). A critical open question is how the same experiences come to be represented differently in neural terms as a function of changing conceptual knowledge.…”
mentioning
confidence: 99%
“…Such representational stability has been found in the hippocampus more generally, such as for olfactory representations when odor information is task-relevant (19). In humans, attention similarly modulates patterns of hippocampal activity, but over voxels measured with functional magnetic resonance imaging (fMRI); for example, attention to different kinds of information induces distinct activity patterns in all hippocampal subfields (10).…”
mentioning
confidence: 96%
“…Specifically, there is growing evidence that attention stabilizes distributed hippocampal representations of task-relevant information (10,13,14). For example, in rodents, distinct ensembles of hippocampal place cells activate when different spatial reference frames are task-relevant (15, 16; see also ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation